Breaking a lance for the psychoacoustics in phoniatrics - F. Klingholz (Archives of Acoustics)
Drawbacks of the acoustical as well as the perceptual voice analysis are discussed. The psychoacoustics is proposed as a new framework for a way out of the dilemma of the traditional voice analysis methods. The relevant features of the psychoacoustic measures with reference to the voice are introduced.